Denser Networks for the Future Internet, the CROWD Approach - de la Oliva, Antonio; Morelli, Arianna; Mancuso, Vincenzo; Draexler, Martin; Hentschel, Tim; Melia, Telemaco; Seite, Pierrick; Cicconetti, Claudio (Lecture Notes of the Institute for Computer Sciences, Social Informatics and Telecommunications Engineering)

Network of Information (NetInf) - An information-centric networking architecture - Dannewitz, Christian; Kutscher, Dirk; Ohlman, B; Farrell, Stephen; Ahlgren, Bengt; Karl, Holger (Computer Communications)

Improving Cooperative Transmission Feasibility by Network Reconfiguration in Limited Backhaul Networks - Dräxler, Martin; Biermann, Thorsten; Karl, Holger (International Journal of Wireless Information Networks)

Trade-off between latency and coverage in cooperative radio access networks - Hohenberger, Till; Herlich, Matthias; Karl, Holger (IEEE International Conference on Advanced Networks and Telecommunications Systems, ANTS 2013, Kattankulathur, India, December 15-18, 2013)

NetIDE: First Steps towards an Integrated Development Environment for Portable Network Apps - M. Facca, Federico; Salvadori, Elio; Karl, Holger; R. Lopez, Diego; Arranda Gutierrez, Pedro; Kostic, Dejan; Riggio, Roberto (Second European Workshop on Software Defined Networks, EWSDN 2013, Berlin, Germany, October 10-11, 2013)

The playground of Wireless Dense networks of the future - Cicconetti, Claudio; Morelli, Arianna; Dräxler, Martin; Karl, Holger; Mancuso, Vincenzo; Sciancalepore, Vincenzo; Gupta, Rohit; de la Oliva, Antonio; Isabel Sanchez, M.; Serrano, Pablo; Roullet, Laurent (2013 Future Network & Mobile Summit, Lisboa, Portugal, July 3-5, 2013)

A topology-aware adaptive deployment framework for elastic applications - Keller, Matthias; Peuster, Manuel; Robbert, Christoph; Karl, Holger (17th International Conference on Intelligence in Next Generation Networks, ICIN 2013, Venice, Italy, October 15-16, 2013)

Energy-Efficient Assignment of User Equipment to Cooperative Base Stations - Herlich, Matthias; Karl, Holger (ISWCS 2013, The Tenth International Symposium on Wireless Communication Systems, Ilmenau, Germany, August 27-30, 2013)

Cross-layer scheduling for multi-quality video streaming in cellular wireless networks - Dräxler, Martin; Karl, Holger (2013 9th International Wireless Communications and Mobile Computing Conference, IWCMC 2013, Sardinia, Italy, July 1-5, 2013)

Anticipatory Buffer Control and Quality Selection for Wireless Video Streaming - Dräxler, Martin; Blobel, Johannes; Dreimann, Philipp; Valentin, Stefan; Karl, Holger (CoRR)

Which Flows Are Hiding Behind My Wildcard Rule? Adding Packet Sampling to OpenFlow - Wette, Philip; Karl, Holger (Proceedings of the ACM SIGCOMM '13)
In OpenFlow [1], multiple switches share the same control plane which is centralized atwhat is called the OpenFlow controller. A switch only consists of a forwarding plane. Rules for forwarding individual packets (called ow entries in OpenFlow) are pushed from the controller to the switches. In a network with a high arrival rate of new ows, such as in a data center, the control trac between the switch and controller can become very high. As a consequence, routing of new ows will be slow. One way to reduce control trac is to use wildcarded ow entries. Wildcard ow entries can be used to create default routes in the network. However, since switches do not keep track of ows covered by a wildcard ow entry, the controller no longer has knowledge about individual ows. To nd out about these individual ows we propose an extension to the current OpenFlow standard to enable packet sampling of wildcard ow entries.

Routing in heterogenen OpenFlow Netzwerken - Wallaschek, Felix

Ressource-Optimized Deployment of Multi-Tier Applications - The Data Rate-Constrained Case - Robbert, Christoph

Reactive Planar Spanner Construction in Wireless Ad Hoc and Sensor Networks - Benter, Markus; Neumann, Florentin; Frey, Hannes (Proceedings of the 32nd IEEE International Conference on Computer Communications (INFOCOM))
Within reactive topology control, a node determines its adjacent edges of a network subgraph without prior knowledge of its neighborhood. The goal is to construct a local view on a topology which provides certain desired properties such as planarity. During algorithm execution, a node, in general, is not allowed to determine all its neighbors of the network graph. There are well-known reactive algorithms for computing planar subgraphs. However, the subgraphs obtained do not have constant Euclidean spanning ratio. This means that routing along these subgraphs may result in potentially long detours. So far, it has been unknown if planar spanners can be constructed reactively. In this work, we show that at least under the unit disk network model, this is indeed possible, by proposing an algorithm for reactive construction of the partial Delaunay triangulation, which recently turned out to be a spanner. Furthermore, we show that our algorithm is message-optimal as a node will only exchange messages with nodes that are also neighbors in the spanner. The algorithm’s presentation is complemented by a rigorous proof of correctness.

How backhaul networks influence the feasibility of coordinated multipoint in cellular networks - Biermann, Thorsten; Scalia, Luca; Choi, Changsoon; Kellerer, Wolfgang; Karl, Holger (IEEE Communications Magazine)

On the Quality of Selfish Virtual Topology Reconfiguration in IP-over-WDM Networks - Wette, Philip; Karl, Holger (Proceedings of the 19th IEEE International Workshop on Local and Metropolitan Area Networks (IEEE LANMAN))
The process of planning a virtual topology for a Wavelength Devision Multiplexing (WDM) network is called Virtual Topology Design (VTD). The goal of VTD is to find a virtual topology that supports forwarding the expected traffic without congestion. In networks with fluctuating, high traffic demands, it can happen that no single topology fits all changing traffic demands occurring over a longer time. Thus, during operation, the virtual topology has to be reconfigured. Since modern networks tend to be large, VTD algorithms have to scale well with increasing network size, requiring distributed algorithms. Existing distributed VTD algorithms, however, react too slowly on congestion for the real-time reconfiguration of large networks. We propose Selfish Virtual Topology Reconfiguration (SVTR) as a new algorithm for distributed VTD. It combines reconfiguring the virtual topology and routing through a Software Defined Network (SDN). SVTR is used for online, on-the-fly network reconfiguration. Its integrated routing and WDM reconfiguration keeps connection disruption due to network reconfiguration to a minimum and is able to react very quickly to traffic pattern changes. SVTR works by iteratively adapting the virtual topology to the observed traffic patterns without global traffic information and without future traffic estimations. We evaluated SVTR by simulation and found that it significantly lowers congestion in realistic networks and high load scenarios.

On Greedy Routing in Degree-bounded Graphs over d-Dimensional Internet Coordinate Embeddings - Autenrieth, Marcus; Frey, Hannes (Proceedings of the Conference on Networked Systems (NetSys))
In this paper we will introduce a new d-dimensional graph for constructing geometric application layer overlay net-works. Our approach will use internet coordinates, embedded using the L∞ -metric. After describing the graph structure, we will show how it limits maintenance overhead by bounding each node’s out-degree and how it supports greedy routing using one-hop neighbourhood information in each routing step. We will further show that greedy routing can always compute a path in our graph and we will also prove that in each forwarding step the next hop is closer to the destination than the current node.

MapReduce in Software Defined Networks - Splietker, Malte

Incorporating feedback from application layer into routing and wavelength assignment algorithms - Wette, Philip; Karl, Holger (Proceedings of the 32nd IEEE International Conference on Computer Communications (INFOCOM))
Preemptive Routing and Wavelength Assignment (RWA) algorithms preempt established lightpaths in case not enough resources are available to set up a new lightpath in a Wavelength Division Multiplexing (WDM) network. The selection of lightpaths to be preempted relies on internal decisions of the RWA algorithm. Thus, if dedicated properties of the network topology are required by the applications running on the network, these requirements have to be known to the RWA algorithm.Otherwise it might happen that by preempting a particular lightpath these requirements are violated. If, however, these requirements include parametersknown only at the nodes running the application, the RWA algorithm cannot evaluate the requirements. For this reason an RWA algorithm is needed which incorporates feedback from the application layer in the preemption decisions.This work proposes a simple interface along with an algorithm for computing and selecting preemption candidates in case a lightpath cannot be established. We reason about the necessity of using information from the application layer in the RWA and present two example applications which benefit from this idea.

Haptics - Hadoop performance testing in concurrent job scenarios - Niklas Vinkemeier, Tim

Emulating Wavelength Division Multiplexing using Openflow - Satya, Suhas

A Local Heuristic for Latency-Optimized Distributed Cloud Deployment - Keller, Matthias; Pawlik, Stefan; Pietrzyk, Peter; Karl, Holger (Proceedings of the 6th International Conference on Utility and Cloud Computing (UCC) workshop on Distributed cloud computing)
In Distributed Cloud Computing, applications are deployed across many data centres at topologically diverse locations to improved network-related quality of service (QoS). As we focus on interactive applications, we minimize the latency between users and an application by allocating Cloud resources nearby the customers. Allocating resources at all locations will result in the best latency but also in the highest expenses. So we need to find an optimal subset of locations which reduces the latency but also the expenses – the facility location problem (FLP). In addition, we consider resource capacity restrictions, as a resource can only serve a limited amount of users. An FLP can be globally solved. Additionally, we propose a local, distributed heuristic. This heuristic is running within the network and does not depend on a global component. No distributed, local approximations for the capacitated FLP have been proposed so far due to the complexity of the problem. We compared the heuristic with an optimal solution obtained from a mixed integer program for different network topologies. We investigated the influence of different parameters like overall resource utilization or different latency weights.

Simulating Cooperative Diversity Protocols for Multi-hop Wireless and Sensor Networks - Khan, Rana Azeem M.; Karl, Holger

Report on Locality in DNS Requests – Evaluation and Impact on Future Internet Architectures - Dannewitz, Christian; Karl, Holger; Yadav, Aditya

Mobile WDM Backhaul Access Networks with Physical Inter-Base-Station Links for Coordinated Multipoint Transmission/Reception Systems - Biermann, T.; Scalia, L. (2011 IEEE Global Telecommunications Conference - GLOBECOM 2011)

Coordinated multipoint multiuser-MIMO transmissions over backhaul-constrained mobile access networks - Choi, Changsoon; Scalia, Luca; Biermann, Thorsten; Mizuta, Shinj (2011 IEEE 22nd International Symposium on Personal, Indoor and Mobile Radio Communications)

CoMP clustering and backhaul limitations in cooperative cellular mobile access networks - Biermann, Thorsten; Scalia, Luca; Choi, Changsoon; Karl, Holger; Kellerer, Wolfgang (Pervasive and Mobile Computing)

Segment-based packet combining: how to schedule a dense relayer cluster? - Willig, Andreas; Karl, Holger; Kipnis, Danil (Wireless Networks)

Average and competitive analysis of latency and power consumption of a queuing system with a sleep mode - Herlich, Matthias; Karl, Holger (Proceedings of the 3rd International Conference on Energy-Efficient Computing and Networking, e-Energy'12, Madrid, Spain, May 9-11, 2012)

Energy Efficient Clustering using a Wake-up Receiver - Blanckenstein, Johannes; Klaue, Jirka; Karl, Holger (European Wireless 2012 - 18th European Conference 2012, April 18-20, 2012, Poznan, Poland.)

On Local Separation of Processing and Storage in Infrastructure-as-a-Service - Künsemöller, Jörn; Karl, Holger (Economics of Grids, Clouds, Systems, and Services - 9th International Conference, GECON 2012, Berlin, Germany, November 27-28, 2012. Proceedings)

Efficiency of On-Path and Off-Path Caching Strategies in Information Centric Networks - Dräxler, Martin; Karl, Holger (2012 IEEE International Conference on Green Computing and Communications, Conference on Internet of Things, and Conference on Cyber, Physical and Social Computing, GreenCom/iThings/CPSCom 2012, Besancon, France, November 20-23, 2012)

OpenNetInf - prototyping an information-centric Network Architecture - Dannewitz, Christian; Herlich, Matthias; Karl, Holger (37th Annual IEEE Conference on Local Computer Networks, Workshop Proceedings, Clearwater Beach, FL, USA, October 22-25, 2012)

Cooperating base station set selection and network reconfiguration in limited backhaul networks - Dräxler, Martin; Biermann, Thorsten; Karl, Holger; Kellerer, Wolfgang (23rd IEEE International Symposium on Personal, Indoor and Mobile Radio Communications, PIMRC 2012, Sydney, Australia, September 9-12, 2012)

Using OMNeT++ for energy optimization simulations in mobile core networks - Dräxler, Martin; Beister, Frederic; Kruska, Stephan; Aelken, J.; Karl, Holger (International ICST Conference on Simulation Tools and Techniques, SIMUTOOLS '12, Sirmione-Desenzano, Italy, March 19-23, 2012)

Quantization techniques for accurate soft message combining - Volkhausen, Tobias; Schinköthe, Kai; Karl, Holger (2012 IEEE Wireless Communications and Networking Conference, WCNC 2012, Paris, France, April 1-4, 2012)

Efficient cooperative relaying in wireless multi-hop networks with commodity WiFi hardware - Volkhausen, Tobias; Dridger, Kornelius; S. Lichte, Hermann; Karl, Holger (10th International Symposium on Modeling and Optimization in Mobile, Ad Hoc and Wireless Networks (WiOpt), Paderborn, Germany, May 14-18, 2012)

Queuing Latency at Cooperative Base Stations - Hohenberger, Till

Optimale Zuteilung von Nutzern zu verteilten Cloud-Standorten - Rojahn, Tobias

Introducing feedback to preemptive routing and wavelength assignment algorithms for dynamic traffic scenarios - Wette, Philip; Karl, Holger
Preemptive Routing and Wavelength Assignment (RWA) algorithms preempt established lightpaths in case not enough resources are available to setup a new lightpath in a Wavelength Division Multiplexing (WDM) network. The selection of lightpaths to be preempted relies on internal decisions of the RWA algorithm. Thus, if dedicated properties of the network topology are required by the applications running on the network, these requirements have to be known by the RWA algorithm. Otherwise it might happen that by preempting a particular lightpath these requirements are violated. If, however, these requirements include parameters only known at the nodes running the application, the RWA algorithm cannot evaluate the requirements. For this reason a RWA algorithm is needed which involves its users in the preemption decisions. We present a family of preemptive RWA algorithms for WDM networks. These algorithms have two distinguishing features: a) they can handle dynamic trafﬁc by on-the-ﬂy reconﬁguration, and b) users can give feedback for reconﬁguration decisions and thus inﬂuence the preemption decision of the RWA algorithm, leading to networks which adapt directly to application needs. This is different from trafﬁc engineering where the network is (slowly) adapted to observed trafﬁc patterns. Our algorithms handle various WDM network conﬁgurations including networks consisting of heterogeneous WDM hardware. To this end, we are using the layered graph approach together with a newly developed graph model that is used to determine conﬂicting lightpaths.

How to manage and Search/Retrieve Information Objects - Dannewitz, Christian; al, et (Architecture and Design for the Future Internet)

Integrating Generic Paths and NetInf - Dannewitz, Christian; al, et (Architecture and Design for the Future Internet)

Power-efficient mobile backhaul design for CoMP support in future wireless access systems - Scalia, Luca; Biermann, Thorsten; Choi, Changsoon; Kozu, Kazuyuki; Kellerer, Wolfgang (2011 IEEE Conference on Computer Communications Workshops (INFOCOM WKSHPS))

Segment-based packet combining in a cluster: To combine or not to combine? - Willig, Andreas; Kipnis, Danil; Karl, Holger (2010 Sixth International Conference on Intelligent Sensors, Sensor Networks and Information Processing)

Scenarios, Research Issues, and Architecture for Ubiquitous Sensing - Kanter, Theo; Kardeby, Victor; Forsström, Stefan; Walters, Jamie (Lecture Notes of the Institute for Computer Sciences, Social Informatics and Telecommunications Engineering)

Ad-hoc, Mobile, and Wireless Networks - 10th International Conference, ADHOC-NOW 2011, Paderborn, Germany, July 18-20, 2011. Proceedings

Content, connectivity, and cloud: ingredients for the network of the future - Ahlgren, Bengt; A. Aranda-Gutierrez, Pedro; Chemouil, Prosper; Oueslati, Sara; M. Correia, L; Karl, Holger; Söllner, Michael; Welin, Annikki (IEEE Communications Magazine)

Research challenges towards the Future Internet - Conti, Marco; Chong, Song; Fdida, Serge; Jia, Weijia; Karl, Holger; Lin, Ying{-}Dar; M{\, Petri; Maier, Martin; Molva, Refik; Uhlig, Steve; Zukerman, Moshe (Computer Communications)

MDHT: A hierarchical name resolution service for information-centric networks - D'Ambrosio, Matteo; Dannewitz, Christian; Karl, Holger; Vercellone, Vinicio (2011 ACM SIGCOMM Workshop on Information-Centric Networking, ICN 2011, Toronto, ON, Canada, August 19, 2011)

Multihop Performance of Cooperative Preamble Sampling MAC(CPS-MAC) in Wireless Sensor Networks - Azeem M. Khan, Rana; Karl, Holger (Ad-hoc, Mobile, and Wireless Networks - 10th International Conference, ADHOC-NOW 2011, Paderborn, Germany, July 18-20, 2011. Proceedings)

Reducing power consumption of mobile access networks with cooperation - Herlich, Matthias; Karl, Holger (2nd International Conference on Energy-Efficient Computing and Networking 2011, e-Energy '11, New York, NY, USA - May 31 - June 01, 2011)

A Game-Theoretical Approach to the Benefits of Cloud Computing - Künsemöller, Jörn; Karl, Holger (Economics of Grids, Clouds, Systems, and Services - 8th International Workshop, GECON 2011, Paphos, Cyprus, December 5, 2011, Revised Selected Papers)

Coding Opportunities from Similar Data in Wireless Cooperation Diversity Systems - Volkhausen, Tobias; Schinköthe, Kai; Karl, Holger (IEEE 8th International Conference on Mobile Adhoc and Sensor Systems, MASS 2011, Valencia, Spain, October 17-22, 2011)

Designing optical metro and access networks for future cooperative cellular systems - Biermann, Thorsten; Scalia, Luca; Karl, Holger (Proceedings of the 14th International Symposium on Modeling Analysis and Simulation of Wireless and Mobile Systems, MSWiM 2011, Miami, Florida, USA, October 31 - November 4, 2011)

The Trade-Off between Power Consumption and Latency in Computer Networks - Herlich, Matthias; Karl, Holger (NETWORKING 2011 Workshops - International IFIP TC 6 Workshops, PE-CRN, NC-Pro, WCNS, and SUNSET 2011, Held at NETWORKING 2011, Valencia, Spain, May 13, 2011, Revised Selected Papers)

Improving CoMP cluster feasibility by dynamic serving base station reassignment - Biermann, Thorsten; Scalia, Luca; Choi, Changsoon; Karl, Holger; Kellerer, Wolfgang (IEEE 22nd International Symposium on Personal, Indoor and Mobile Radio Communications, PIMRC 2011, Toronto, ON, Canada, September 11-14, 2011)

Backhaul Design and Controller Placement for Cooperative Mobile Access Networks - Biermann, Thorsten; Scalia, Luca; Widmer, J.; Karl, Holger (Proceedings of the 73rd IEEE Vehicular Technology Conference, VTC Spring 2011, 15-18 May 2011, Budapest, Hungary)

Backhaul network pre-clustering in cooperative cellular mobile access networks - Biermann, Thorsten; Scalia, Luca; Choi, Changsoon; Karl, Holger; Kellerer, Wolfgang (12th IEEE International Symposium on a World of Wireless, Mobile and Multimedia Networks, WOWMOM 2011, Lucca, Italy, 20-24 June, 2011)

Defining and Deploying Complex Applicances in Multi-Site Cloud Environments - Peuster, Manuel

Load Balancing in P2P Networks: Using Statistics to Fight Data and Execution Skew - Warneke, Daniel; Dannewitz, Christian (Journal of Advances in Information Technology)

Complex Queries in P2P Networks with Resource-Constrained Devices - Dannewitz, Christian; Biermann, Thorsten; Dräxler, Martin; Karl, Holger (Journal of Advances in Information Technology)

Selected properties of a joint congestion controller for TCP connections - Savorić, Michael; Karl, Holger; Wolisz, Adam (Providing Quality of Service in Heterogeneous Environments, Proceedings of the 18th International Teletraffic Congress - ITC-18)

ANALYSING CAPACITY IMPROVEMENTS IN WIRELESS NETWORKS BY RELAYING - Karl, Holger; MENGESHA, S. (Wireless LANs and Home Networks)

Flexible Resource Management for Self-X Systems: An Evaluation - Oberthür, Simon; Zaremba, Leszek; Lichte, Hermann Simon (2010 13th IEEE International Symposium on Object/Component/Service-Oriented Real-Time Distributed Computing Workshops)

Secure Naming for a Network of Information - Dannewitz, Christian; Golic, Jovan; Ohlman, Borje; Ahlgren, Bengt (2010 INFOCOM IEEE Conference on Computer Communications Workshops)

Cooperative feedback to improve capacity and error rate in multiuser diversity systems - an OFDM case study - Valentin, Stefan; Karl, Holger (European Transactions on Telecommunications)

Cooperative feedback to improve capacity and error rate in multiuser diversity systems - an OFDM case study - Valentin, Stefan; Karl, Holger (European Transactions on Telecommunications)

Expected interference in wireless networks with geometric path loss: a closed-form approximation - S. Lichte, Hermann; Valentin, Stefan; Karl, Holger (IEEE Communications Letters)

Automated Development of Cooperative MAC Protocols - A Compiler-Assisted Approach - Simon Lichte, Hermann; Valentin, Stefan; Karl, Holger (Mobile Networks and Applications)

Concept and Prototype for a Real-Time Enabled Publish/Subscribe System - Andree, Matthias; Gebel, Alexander; Karl, Holger (10th IEEE International Conference on Computer and Information Technology, CIT 2010, Bradford, West Yorkshire, UK, June 29-July 1, 2010)

Risk Aware Overbooking for Commercial Grids - Birkenheuer, Georg; Brinkmann, Andre; Karl, Holger (Job Scheduling Strategies for Parallel Processing - 15th International Workshop, JSSPP 2010, Atlanta, GA, USA, April 23, 2010, Revised Selected Papers)

Fading-resistant low-latency broadcasts in wireless multihop networks: the probabilistic cooperation diversity approach - S. Lichte, Hermann; Frey, Hannes; Karl, Holger (Proceedings of the 11th ACM Interational Symposium on Mobile Ad Hoc Networking and Computing, MobiHoc 2010, Chicago, IL, USA, September 20-24, 2010)

FIT: Future Internet Toolbox - Biermann, Thorsten; Dannewitz, Christian; Karl, Holger (Testbeds and Research Infrastructures. Development of Networks and Communities - 6th International ICST Conference, TridentCom 2010, Berlin, Germany, May 18-20, 2010, Revised Selected Papers)

Prototyping with the Future Internet Toolbox - Dannewitz, Christian; Biermann, Thorsten; Dräxler, Martin; Beister, Frederic; Karl, Holger (Testbeds and Research Infrastructures. Development of Networks and Communities - 6th International ICST Conference, TridentCom 2010, Berlin, Germany, May 18-20, 2010, Revised Selected Papers)

Network coding in passive optical networks - Miller, Konstantin; Biermann, Thorsten; Woesner, Hagen; Karl, Holger (Network Coding (NetCod), 2010 IEEE International Symposium on)

RiaS: overlay topology creation on a PlanetLab infrastructure - Lischka, Jens; Karl, Holger (Proceedings of the second ACM SIGCOMM workshop on Virtualized infrastructure systems and architectures)

Energy efficiency model of network-coded cooperation in wireless sensor networks - Woldegebreal, Dereje H; Karl, Holger (Sensor Technologies and Applications (SENSORCOMM), 2010 Fourth International Conference on)

Cooperative communication to improve reliability and efficient neighborhood wakeup in wireless sensor networks - Khan, Rana Azeem M; Karl, Holger (Proceedings of the Fourth International Conference on Mobile Ubiquitous Computing (UBICOMM 2010))

Improving Network Coded Cooperation by Soft Information - Volkhausen, Tobias; Woldegebreal, Dereje H.; Karl, Holger (2009 6th IEEE Annual Communications Society Conference on Sensor, Mesh and Ad Hoc Communications and Networks Workshops)

Combining for Cooperative WLANs - A Reality Check Based on Prototype Measurements - Valentin, S.; Woldegebreal, D. H.; Volkhausen, T.; Karl, Holger (2009 IEEE International Conference on Communications Workshops)

Creating Butterflies in the Core – A Network Coding Extension for MPLS/RSVP-TE - Biermann, Thorsten; Schwabe, Arne; Karl, Holger (NETWORKING 2009)

Modeling obstacles in INET/Mobility framework: motivation, integration, and performance - Lichte, Hermann S.; Weide, Jannis (Proceedings of the Second International ICST Conference on Simulation Tools and Techniques)

Design considerations for a network of information - Ahlgren, Bengt; Vercellone, Vinicio; D'Ambrosio, Matteo; Marchisio, Marco; Marsh, Ian; Dannewitz, Christian; Ohlman, Börje; Pentikousis, Kostas; Strandberg, Ove; Rembarz, René (Proceedings of the 2008 ACM CoNEXT Conference on - CONEXT '08)

Flow Synchronization for Network Coding - Biermann, Thorsten; Dräxler, Martin; Karl, Holger (Journal of Communications)

Cooperative Wireless Networking Beyond Store-and-Forward - Valentin, Stefan; S. Lichte, Hermann; Karl, Holger; Vivier, Guillaume; Simoens, Sebastien; Vidal, Josep; Agustin, Adrian (Wireless Personal Communications)

An Adaptive Resource/Performance Trade-Off for Resolving Complex Queries in P2P Networks - Biermann, Thorsten; Dannewitz, Christian; Karl, Holger (Proceedings of IEEE International Conference on Communications, ICC 2009, Dresden, Germany, 14-18 June 2009)

Rate-Per-Link Adaptation in Cooperative Wireless Networks with Multi-Rate Combining - S. Lichte, Hermann; Valentin, Stefan; von Malm, Holger; Karl, Holger; Bin Sediq, Akram; Aad, Imad (Proceedings of IEEE International Conference on Communications, ICC 2009, Dresden, Germany, 14-18 June 2009)

The Gain of Overbooking - Birkenheuer, Georg; Brinkmann, Andre; Karl, Holger (Job Scheduling Strategies for Parallel Processing, 14th International Workshop, JSSPP 2009, Rome, Italy, May 29, 2009. Revised Papers)

Analyzing space/capacity tradeoffs of cooperative wireless networks using a probabilistic model of interference - Simon Lichte, Hermann; Valentin, Stefan; Karl, Holger; Aad, Imad; Widmer, J. (Proceedings of the 12th International Symposium on Modeling Analysis and Simulation of Wireless and Mobile Systems, MSWiM 2009, Tenerife, Canary Islands, Spain, October 26-19, 2009)

Creating Butterflies in the Core - A Network Coding Extension for MPLS/RSVP-TE - Biermann, Thorsten; Schwabe, Arne; Karl, Holger (NETWORKING 2009, 8th International IFIP-TC 6 Networking Conference, Aachen, Germany, May 11-15, 2009. Proceedings)

A virtual network mapping algorithm based on subgraph isomorphism detection - Lischka, Jens; Karl, Holger (Proceedings of the 1st ACM SIGCOMM Workshop on Virtualized Infrastructure Systems and Architectures, VISA 2009, Barcelona, Spain, August 17, 2009)

Cooperation and coding framework - Biermann, Thorsten; Polgar, Zsolt Alfred; Karl, Holger (Communications Workshops, 2009. ICC Workshops 2009. IEEE International Conference on)

Combining for cooperative WLANs-a reality check based on prototype measurements - Valentin, Stefan; Woldegebreal, Dereje H; Volkhausen, Tobias; Karl, Holger (Communications Workshops, 2009. ICC Workshops 2009. IEEE International Conference on)

Improving network coded cooperation by soft information - Volkhausen, Tobias; Woldegebreal, Dereje H; Karl, Holger (Sensor, Mesh and Ad Hoc Communications and Networks Workshops, 2009. SECON Workshops' 09. 6th Annual IEEE Communications Society Conference on)

Statistics-based ID management for load balancing in structured P2P networks - Warneke, Daniel; Dannewitz, Christian (2009 IEEE 34th Conference on Local Computer Networks)

Extended Results on an Adaptive Resource/Performance Trade-Off for Resolving Complex Queries in P2P Networks - Biermann, Thorsten; Dannewitz, Christian; Karl, Holger

Employing WS-BPEL Design Patterns for Grid Service Orchestration using a Standard WS-BPEL Engine and a Grid Middleware - Brinkmann, André; Gudenkauf, Stefan; Hasselbring, Wilhelm; Höing, André; Karl, Holger; Kao, Odej; Nitsche, Holger; Scherp, Guido (Proc. Cracow Grid Workshop (CGW))

Proceedings of the 1. GI/ITG KuVS Fachgespräch Virtualisierung

Mobile Cooperative WLANs - MAC and Transceiver Design, Prototyping, and Field Measurements - Valentin, Stefan; Lichte, Hermann S.; Warneke, Daniel; Biermann, Thorsten; Funke, Rafael; Karl, Holger (2008 IEEE 68th Vehicular Technology Conference)

Integrating Multiuser Dynamic OFDMA into IEEE 802.11 WLANs - LLC/MAC Extensions and System Performance - Valentin, S.; Freitag, T.; Karl, Holger (2008 IEEE International Conference on Communications)